Market Anomalies in Kompas100 Stock Returns and Trading Volume (2023–2024) Emphasizing Calendar Effects - Endang Ruhiyat; Refina Tasari Samosir; Suripto Suripto; Holiawati Holiawati; Aris Sanulika (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Main Objectives: This study aims to examine the presence of market anomalies—specifically the Day-of-the-Week Effect, Turn-of-the-Month Effect, and Turn-of-the-Year Effect—on stock returns and trading volume in the Kompas100 Index during the 2023–2024 period. Background Problems: Financial markets are generally considered efficient in processing available information. However, the presence of anomalies, particularly those arising from irrational investor behavior, indicates deviations from market efficiency. Novelty: By integrating all three calendar anomalies, this study provides a more comprehensive analysis of their influence on the capital market. Research Methods: This study employs a quantitative associative approach using panel data regression analysis. The data are obtained from companies listed in the Kompas100 Index of the Indonesia Stock Exchange (IDX) during the 2023 to 2024 period. A non-probability sampling technique is applied, specifically purposive sampling. Finding/Results: The results reveal significant effects of several anomalies—particularly the Monday Effect, January Effect, and early-month periods—on both stock returns and trading volume. These findings support behavioral finance theory and challenge the Efficient Market Hypothesis. Conclusion: This study concludes that the Indonesian stock market exhibits behavior-driven anomalies that create short-term trading opportunities.